Potential Ecology Suitability Distribution of Forage Availability for Dairy Cattle. Case study: Lembang District Area, West Java - Al Zahra, W.; Saefuddin, A.; Abdullah, L. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2015)
Dairy cattle have a highly depend on forage for its daily diet that will influence milk production. Therefore forage supply is the core issue in dairy farming productivity in Indonesia. Hence, it is very important in securing forage supply in order for sustainability of dairy farming. However, the forage availability is becoming rare due to the limitation of farming land owned by the farmers. The aim of this research was to determine geospatial distribution of forage availability for dairy cattle in Lembang Area, West Java. GIS software (ArcView 3.2) was used in this research. Secondary data, including maps (Land use, rainfall, slope, ect) were required in this research. As we know that the ecological suitability was the primary requirements for forage management. Moreover, the ecological suitability was assessed by criteria classification in order to achive optimum forage production. The result of map overlapping has resulted the potential ecology suitability for forage management. Furthermore, land suitability was physically divided into 4 classes; highly suitable (S1), moderate suitable (S2), marginally suitable (S3), not suitable (N) and constrain (C) that became the restriction point for forage management.Keywords : Dairy Cattle, Forage, Geographic Information System